TAPS Ban and Media Literacy to Protect Youth from Tobacco Industry Inducement - Nurjanah, Nurjanah; Sugihantono, Anung; Widjanarko, Bagoes; Handayani, Novia; Musthofa, Syamsulhuda Budi; Puspitaningtyas, Sheila Indah; Wulandari, Anastasia; Fadhilah, Nur; Fajriyah, Nuniek Nizmah; Permadi, Yulian Wahyu; Subekti, Ratih; Faozan, Amir (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: The Indonesia Health Survey 2023 indicates that around 70 million people in the country smoke, with 7.2% aged 10 to 18, and Central Java province reports one of the highest child prevalence rates in Indonesia at 9.6%. Tobacco Advertising, Promotion, and Sponsorship (TAPS) influence intention to smoke, and on the other hand, Smoking Media Literacy (SML) can be a shield for youth to protect them from tobacco industry inducement. Methods: This study aims to evaluate the impact of TAPS exposure and SML on smoking intention. This cross-sectional study includes 1,014 students from ten junior high schools, eleven high schools, and five universities located in the three primary municipalities of Central Java Province. A stratified sampling method was used to choose the participants, and data was collected through a self-administered questionnaire. Results: The students were most frequently exposed to TAPS through outdoor media such as billboards and banners, followed by displays at points of sale and online platforms like social media and websites. The logistic regression found that Higher media literacy is associated with a decreased likelihood of intending to smoke, with (OR 0.60). Conversely, exposure to tobacco advertising, promotion, and sponsorship (TAPS) increases intending to smoke by approximately 55% (OR 1.55). The intention to smoke is the most potent predictor of whether an individual has ever smoked (OR 9.91). Conclusion: The low media literacy increases vulnerability to tobacco marketing, while exposure to tobacco advertising and promotion significantly heightens the likelihood of intending to smoke. The strong association between smoking intention and highlights the critical importance of early preventative measures. Targeted strategies such as media literacy education and a total TAPS ban are essential to curb the rising trend of tobacco use among Indonesian youth.